How effectively do public works programs transfer benefits to the poor? evidence from South Africa - Haddad, Lawrence J.; Adato, Michelle (International Food Policy Research Institute, 2001)
This paper uses project and household data to examine the ability of 100 or so public works projects in Western Cape Province, South Africa, to target benefits—both direct and indirect—to those living below the poverty line. We find that public works projects generally outperform hypothetical untargeted cash transfers in this regard under a wide range of assumptions about underlying parameters.